Strategies to Overcome Challenges in Utilizing SIPD: Achieving High-Quality Accrual-Based Financial Reporting - Naida, Nasrun; Sartika, Dewi (Society : Jurnal Pengabdian Masyarakat, 2025)
This study explores the modernization of regional financial management in Tojo Una-Una Regency as a strategic initiative to enhance transparency, accountability, and efficiency in governance. The Regional Government Information System (SIPD), particularly the Accounting and Reporting (AKLAP) module, has been implemented since 2022 to support accrual-based financial reporting in compliance with government accounting standards. Despite its potential, several challenges remain, including a lack of skilled human resources and insufficient technical training for system operators, which hinder effective integration and reporting accuracy. Using a descriptive qualitative method with an inductive approach, this study draws on interviews and observations to identify barriers and propose optimization strategies. Findings reveal that unequal access to technology across Regional Apparatus Organizations (OPD) and limited operator competence are significant obstacles. To address these issues, the study recommends intensive training for SIPD operators and enhanced technological infrastructure at the OPD level. These measures aim to improve the quality and reliability of financial management, advancing a more transparent and accountable system. This research contributes novel insights into overcoming practical challenges in regional financial management, offering actionable strategies for similar contexts.